KEPASTIAN HUKUM IZIN USAHA PERTAMBANGAN KHUSUS/IUPKStudi: IUPK sebagai Kelanjutan Kontrak Karya dan Perjanjian Karya Pengusahaan Pertambangan Batubara dalam UU Minerba - Annisa Thurfah Asilah (2021)
After the promulgation of Law Number 3 of 2020 many people highlighted the addition of Article 169A wich explains the guarantee of extension through special mining business license (IUPK) for contract of work (KK) and work agreement for coal mining exploitation (PKP2B) which will expire. However actually the guarantee of extension is not automatically given but through considerations mandated by the law. The formulation of the problem raised in this study is about the legal certainty of granting IUPK as a continuation of contract/agreement operations and how legal protection for KK and PKP2B if the application for extension of contract/agreement is rejected by the Ministry of Energy and Mineral Resources (ESDM). This study uses a normative juridical research method through literature study with a statutory approach. The result of this study indicate a vagueness of norms which results in the absence of legal certainty in Article 169A of the Minerba Law which regulates IUPK as a continuation of contract/agreement operations. The provisions regarding these rules must be explained using clear and firm phrases in the Government Regulation as derivative rules for implementing the Minerba Law so as not to cause multiple interpretations in order to provide the legal certainty and protection for mining business actors. Key words: Minerba, Business License, Mining.